CONSTITUTION IN LEGAL POLITICAL PERSPECTIVE - Zaman, Nurus (TRUNOJOYO LAW REVIEW, 2022)
In this study there are 2 (two) problems studied. First, what is the form or form of legal politics in the 1945 Constitution. Second, what is the nature of legal politics in the 1945 Constitution. This research uses normative legal research. The research results obtained: First, the form or form of legal politics in the constitution as a means in order to achieve the goals of the state, namely the interests of the nation and state, the basic law of legal politics in the constitution comes from the values and character of the nation, taking into account the legal system adopted. Second, the legal politics in the 1945 Constitution is not rigid or permanent, but the nature of legal politics in the constitution is open, that is, it can adapt to the situation and conditions of its era, either through the method of interpretation or through the method of change.